Exercise's effect on mobility disability in older adults with and without obesity: The LIFE study randomized clinical trial. Issue 7 (July 2017) - Kritchevsky, Stephen B.; Lovato, Laura; Handing, Elizabeth P.; Blair, Steven; Botoseneanu, Anda; Guralnik, Jack M.; Liu, Christine; King, Abby; Marsh, Anthony P.; Pahor, Marco; Rejeski, W. Jack; Spring, Bonnie; et al.
Abstract : Objective: Some data suggest that obesity blunts the benefits of exercise on mobility in older adults. This study tested the homogeneity of the effect of a physical activity intervention on major mobility disability (MMD) across baseline obesity classifications in the Lifestyle Interventions and Independence for Elders (LIFE) Study. LIFE randomized 1, 635 sedentary men and women aged 70 to 89 years to a moderate‐intensity physical activity (PA) or health education program. Methods: MMD, defined as the inability to walk 400 m, was determined over an average follow‐up of 2.6 years. Participants were divided into four subgroups: (1) nonobese (BMI < 30 kg/m 2 ; n  = 437); (2) nonobese with high waist circumference (WC > 102 cm [men],  > 88 cm [women]; n  = 434); (3) class 1 obesity (30 kg/m 2  ≤ BMI < 35 kg/m 2 ; n  = 430); and (4) class 2 + obesity (BMI ≥ 35 kg/m 2 ; n  = 312). Cox proportional hazard modeling was used to test an obesity by intervention interaction. Results: The PA intervention had the largest benefit in participants with class 2 + obesity (hazard ratio 0.69, 95% confidence interval 0.48, 0.98). However, there was no statistically significant difference in benefit across obesity categories. Conclusions: A structured PA program reduced the risk of MMD even in older adults with extreme obesity.